Strengthening relationships between couples to respond to domestic violence: a commentary on policy changes needed to support this evolution - Barth, Richard P. (Journal of family violence, 2023)
Broad calls to narrow the role of police in American society have begun to include arguments to reduce the carceral responding to intimate partner violence (IPV) and add a stronger social response. The field’s improved understanding of lethality risk assessment; better classification of offender risk by past involvement with general violence or family only violence; and positive findings from trials of relationship strengthening interventions as couples counseling, restorative justice practices, and mediation, call for exploring relationship-strengthening approaches to complement more carceral approaches. Yet, a half century of adherence to traditional IPV service approaches that have steered away from relationship strengthening has generated an array of procedures and policies that need to change before the IPV services field can broaden and become more responsive. These changes are likely to be more fitting across racial and cultural groups and more suited for those seeking to improve relationship safety. This paper reviews these trends and considers legislative remedies that would facilitate the emergence of additional safe, empowering, relationship-responsive, trauma sensitive additions to IPV services.